The Integration Of The Ballast Water Management Convention 2004 Into State Responsibility To Ensure The Marine Environmental Protection : Case Study In Indonesia - Andi Maulana; Nellyana Roesa (Fakultas Hukum Universitas Syiah Kuala, 2018)
Invasive aquatic species present a major threat to the marine ecosystems, and shipping has been identified as a major pathway for introducing species to new environments. Such harmful species is transferred through ship’s ballast water. When ship’s ballast water is discharged into a new environment in destination port, invasive aquatic species contained in ballast water will cause damage to host environment. In 2004, an international treaty was established to overcome this issue, that is the Ballast Water Management Convention 2004, with Indonesia as one of state parties to the Convention by ratifying the Convention into Presidential Decree No. 132 of 2015. There is a case where the introduction of ballast water damaged marine ecosystem and killed marine biota in Gulf Lampung in 2012. This damage shall be an alert for Indonesia to take immediate action to integrate the Convention into its national legislation. This thesis aims to examine how Indonesia ensure shipping operation under their territory comply with the Ballast Water Management Convention and to identify any challenges to implement the Convention properly. This research is conducted through normative method. It focuses on library research to collect, reading, citing and analyzing data that are related to the subject of research beside primary and tertiary data. After conducting the research, it is found that Indonesia has two roles according to the Ballast Water Management Convention, as flag state and port state. As a flag state, integrating the Convention into national law shall be carried out immediately to comply with the Convention and also to conduct survey and certification of ship. As a port state, Indonesia needs to carry out inspection to foreign ships that apply the Convention with no more favourable treatment is given to the ships from non-state parties. However, the government have to deal with lack of adequate facilities and skillful human resources to support the enforcement of Ballast Water Management Convention. It is suggested that Indonesia shall review its national legislation in order to accommodate any obligations as flag state and port state pursuant to the Ballast Water Management Convention. Furthermore, the government must develop adequate testing facility to ensure that Ballast Water Management System Certificate issued by the government is consistent with the Convention. Another important issue is to deploy enough qualified Port State Control personnels in every national port visited by foreign ships to conduct appropriate ship inspection.